Acceptability of an internet-delivered intervention for adjustment disorder and its role as predictor of efficacy - Rachyla, Iryna; Mor, Sonia; Botella, Cristina; Castilla, Diana; Quero, Soledad (Frontiers in Virtual Reality, 2022)
Background: Internet-delivered interventions offer a feasible way to facilitate access to mental healthcare and considerable evidence supports their effectiveness for the treatment of different mental disorders. However, potential users’ attitudes toward these interventions are crucial for their successful implementation. A better understanding of factors related to treatment acceptance and adherence is required to exploit the full potential of internet interventions. Hence, the aim of the present work was to analyze the acceptability of a therapist-guided internet-delivered CBT intervention for adjustment disorder and its impact on treatment outcomes. Methods: The acceptability was estimated from the acceptance to participate in the randomized controlled trial addressed to explore the effectiveness of the internet intervention in question. Other indicators of acceptability were treatment adherence, expectations, satisfaction, and opinion reported by 34 participants from the trial. Results: Willingness to try an internet intervention was observed and 76.5% of participants completed all seven treatment modules. Less positive initial expectations did not reduce treatment effectiveness, yet they might have led to treatment abandonment. Overall, participants were satisfied with the internet intervention and perceived it as a useful, comfortable and attractive way of receiving psychological assistance. Treatment modules aimed at promoting identification with the treatment goals, relapse prevention, and change in the meaning of the stressor were found to be related to posttraumatic growth and increase in positive affect and quality of life. Participants also expressed that the intervention required considerable motivation. In this regard, therapeutic support was perceived as an important adherence facilitator. Conclusion: The findings from this work support the suitability of internet interventions for the treatment of adjustment disorder. However, further research is required in order to develop guidelines for the design of more attractive and engaging internet interventions.